Sound Velocity Corrections for the North Sea Surveyor - Bailey, R. T. (The International Hydrographic Review, 2015)
There is a mass of learned information about the velocity of sound in sea water. There are various formulae relating to temperature and salinity, and various ways of calculating the mean velocity for the water column. The formulae, needless to say, give different answers, but does it matter? This article takes a simplified look at velocity corrections for the surveyor on the Continental Shelf — to which Matthews Tables do not apply — and has a special application to the North Sea.